EFFECT OF NOZZLE TYPE AND SOME LOCALLY USED SURFACTANTS ON THE SPRAY QUALITY - & et al., Subr (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to compare two spreading agents (Tween 20 (T) and dishwashing detergent (D)) which are commonly used in agricultural researches in Iraq and sometimes are used by the local spray applicators. Moreover, the universalflat fan nozzle (UNI) was compared with the air induction nozzle (AI) concerning the quality of the spray produced. The treatments included three concentrations (1.0%; 0.1% and 0.01% vol /vol %) of each spreading material beside the control treatment (water only). Spray quality was evaluated by using the water sensitive papers (WSP), and DepositScan software was used to analyze the scanned photos of WSP. Theevaluated parameters related to the spray quality included: spray coverage (%); spray density (Deposits/cm²); average droplet diameter (DV.5) and deposition of droplets (µL/cm²). Moreover, the penetration rate was also calculated by comparing the deposition quantity between two levels of WSP on the plant canopy (upper and middle level) while the deposition which reached the ground was considered as losses rate. The results have shown that adding Tween 20 spreading agent to the spray solution has produced more deposits per square centimeter and more penetration rate of spray inside the plants canopy than the detergent and control. Moreover, the UNI type nozzle produced higher coverage percentage and number of deposits per square centimeter than AI nozzle.